Sağ Popülizm ve Toplumsal Cinsiyet Karşıtı Hareketlerin Birlikteliğinde AKP Hükümetlerinin Aile Siyaseti ve Popülist Siyasal Mobilizasyonu - KOUROU, NUR SİNEM (My University, 2020)
Sağ popülizm ve toplumsal cinsiyet karşıtı hareketler arasındaki ilişki, son on yıllarda dünya siyasetinin gündeminde oldukça popüler bir konu olmuştur. Bu makale, Adalet ve Kalkınma Partisi (AKP) döneminde Türkiye'de bu ikili hareket arasındaki ilişkinin nasıl çerçevelendiğinin partinin kadın politikaları özelinde ve parti mobilizasyonu bağlamında geliştirdiği anti-feminist popülist stratejinin izini sürüyor. Türkiye ile dünyadaki diğer örnekler arasında diyalog kurmaya çalışan bu makale, aynı zamanda Türkiye’deki farklı pratiklerin de altını çiziyor. Makale 2019 yılında başlayan AKP’nin popülizmi bir mobilizasyon aracı olarak kullanmasına odaklanan araştırmama dayanıyor. 2019 yerel seçimleri öncesi AKP’nin İstanbul’da yürüttüğü seçim çalışmalarını takip ederek yürüttüğüm araştırmada partinin farklı ilçelerdeki Kadın Kolları teşkilatlarının faaliyetlerini merkeze aldım. AKP’nin hem iktidarda olduğu hem de muhalefette olduğu ilçelerde gözlem ve görüşmelerimi sürdürdüm. İstanbul özelinde farklı ilçelerde geçen saha çalışmasının yanında AKP İstanbul İl Başkanlığı’nın yayın organı olan haftalık dergi AK Bülten’in 2009-2019 yılları arasında yayınlanan yaklaşık 500 sayısı da analize dahil edilmiştir. Bu makale, siyasette toplumsal cinsiyetin eşitliği merkezinden aile merkezci anlayışa geçişi ve bunların nasıl bir siyasi mobilizasyona dönüştüğünü Türkiye örneğinde göstermektedir. Bunu yaparken de anti-feminist popülizmin AKP özelinde ideolojik bir söylemin ötesinde bir oy devşirme stratejisine dönüştürüldüğünü iddia etmektedir.

The relationship between right-wing populism and anti-gender movements has been quite a popular issue in the agenda of world politics since the last decades. This article traces how this dual movement and the relationship have been framed in Turkey under Justice and Development Party (AKP) rule, and the anti-feminist populist strategy developed by the party in terms of women’s policies and party mobilization. By seeking to engage in dialogue between Turkey and its counterparts, this article also underlines what Turkey does differently. This article is based on my research that started in 2019 focusing on the AKP’s use of populism as a mobilization tool. In the research, I followed the election activities of the AKP in Istanbul and particularly focused on the activities of the party’s women’s branches in different districts before the 2019 local elections. I conducted my observations and interviews in different districts. In addition to the fieldwork, approximately 500 issues (2009-2019) of the weekly journal AK Bulten, which is the publication of the AKP Istanbul Provincial Headquarter, were included in the analysis. Emphasizing the similarities and differences of practices in the world in terms of right-wing populism and anti-gender movements, this article shows the transition from gender equality center to family-centered understanding in politics and how these turned into a political mobilization in the example of Turkey, AKP. This article illustrates the shift in the politics from gender mainstreaming to family mainstreaming and how these have turned into a political mobilization in Turkey. In doing so, it argues that anti-feminist populism has been transformed into a vote-harvesting strategy beyond an ideological discourse in the case of the AKP.
In the Alliance of Right-Wing Populism and Antigender Movements AKP’s Family Mainstreaming and Populist Political Mobilization
Keywords: Toplumsal Cinsiyet Karşıtı Hareketler; Popülizm; AKP; Muhafazakarlık; Kadın ve Siyaset; Anti-gender movements; Populism; Conservatism; Women and Politics